KINERJA PEGAWAI TERHADAP PELAYANAN PUBLIK PADA DINAS BINA MARGA, CIPTA KARYA, TATA RUANG, PERTANAHAN DAN PERUMAHAN RAKYAT KABUPATEN SIDENRENG RAPPANG - Agustina Syamsuddin; Kamaruddin Sellang; Erfina Erfina (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the performance of employees towards public services and the factors that affect the performance of employees towards public services at the Department of Highways, Cipta Karya, Spatial Planning, Land and Public Housing, Sidenreng Rappang Regency. The population in this study were 93 people. The sampling technique used was random sampling or random sampling. This type of research is descriptive quantitative. Data collection techniques are observation, questionnaires, literature study and interviews. The data analysis technique used is descriptive analysis, simple linear regression using a Likert scale. The results showed that the performance of employees towards public services at the Department of Highways, Cipta Karya, Spatial Planning, Land and Public Housing of Sidenreng Rappang Regency was quite good. Where the percentage of employee performance is 60.85% in good category, while public service is 62.28% in good category, As for the factors that affect employee performance, namely the ability factor with an average result of 58.4% and the motivation factor with an average result of 57.2%. By looking at the percentage results of 57.8%, the factors that affect employee performance are in the unfavorable category.